Anticoagulation and Antiplatelet Therapy for Prevention of Venous and Arterial Thrombotic Events in Critically Ill Patients With COVID-19: COVID-PACT. Issue 18 (29th August 2022) - Bohula, Erin A.; Berg, David D.; Lopes, Mathew S.; Connors, Jean M.; Babar, Ijlal; Barnett, Christopher F.; Chaudhry, Sunit-Preet; Chopra, Amit; Ginete, Wilson; Ieong, Michael H.; Katz, Jason N.; Kim, Edy Y.; et al.
Abstract : Background: The efficacy and safety of prophylactic full-dose anticoagulation and antiplatelet therapy in critically ill COVID-19 patients remain uncertain. Methods: COVID-PACT (Prevention of Arteriovenous Thrombotic Events in Critically-ill COVID-19 Patients Trial) was a multicenter, 2×2 factorial, open-label, randomized-controlled trial with blinded end point adjudication in intensive care unit–level patients with COVID-19. Patients were randomly assigned to a strategy of full-dose anticoagulation or standard-dose prophylactic anticoagulation. Absent an indication for antiplatelet therapy, patients were additionally randomly assigned to either clopidogrel or no antiplatelet therapy. The primary efficacy outcome was the hierarchical composite of death attributable to venous or arterial thrombosis, pulmonary embolism, clinically evident deep venous thrombosis, type 1 myocardial infarction, ischemic stroke, systemic embolic event or acute limb ischemia, or clinically silent deep venous thrombosis, through hospital discharge or 28 days. The primary efficacy analyses included an unmatched win ratio and time-to-first event analysis while patients were on treatment. The primary safety outcome was fatal or life-threatening bleeding. The secondary safety outcome was moderate to severe bleeding. Recruitment was stopped early in March 2022 (≈50% planned recruitment) because of waning intensive care unit–level COVID-19 rates. Results: At 34 centers in the United States, 390 patients were randomly assigned between anticoagulation strategies and 292 between antiplatelet strategies (382 and 290 in the on-treatment analyses). At randomization, 99% of patients required advanced respiratory therapy, including 15% requiring invasive mechanical ventilation; 40% required invasive ventilation during hospitalization. Comparing anticoagulation strategies, a greater proportion of wins occurred with full-dose anticoagulation (12.3%) versus standard-dose prophylactic anticoagulation (6.4%; win ratio, 1.95 [95% CI, 1.08–3.55]; P =0.028). Results were consistent in time-to-event analysis for the primary efficacy end point (full-dose versus standard-dose incidence 19/191 [9.9%] versus 29/191 [15.2%]; hazard ratio, 0.56 [95% CI, 0.32–0.99]; P =0.046). The primary safety end point occurred in 4 (2.1%) on full dose and in 1 (0.5%) on standard dose ( P =0.19); the secondary safety end point occurred in 15 (7.9%) versus 1 (0.5%; P =0.002). There was no difference in all-cause mortality (hazard ratio, 0.91 [95% CI, 0.56–1.48]; P =0.70). There were no differences in the primary efficacy or safety end points with clopidogrel versus no antiplatelet therapy. Conclusions: In critically ill patients with COVID-19, full-dose anticoagulation, but not clopidogrel, reduced thrombotic complications with an increase in bleeding, driven primarily by transfusions in hemodynamically stable patients, and no apparent excess in mortality. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04409834.